2022
DOI: 10.1101/2022.10.21.512368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Career Self-Efficacy Disparities in Underrepresented Biomedical Scientist Trainees

Abstract: The present study examines racial, ethnic, and gender disparities in career self-efficacy amongst 6077 US citizens and US naturalized graduate and postdoctoral trainees. Respondents from biomedical fields completed surveys administered by the National Institutes of Health Broadening Experiences in Scientific Training (NIH BEST) programs across 17 US institutional sites. Graduate and postdoctoral demographic and survey response data were examined to evaluate the impact of intersectional identities on trainee ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…In our analysis, the internal factors cited by students as reasons for changing career goals contribute to formation of self-efficacy, and the external factors cited by students as reasons for changing career goals align with their outcomes expectations about attaining a career as a PI. Several studies designed to examine career interest formation through the lens of SCCT have also shown that social identity influences career interests of biomedical scientists, 15,16,28,33,34 though we did not attempt to analyze the role of social identity in our population, as it is beyond the scope of this study.…”
Section: Changing Career Goalsmentioning
confidence: 99%
“…In our analysis, the internal factors cited by students as reasons for changing career goals contribute to formation of self-efficacy, and the external factors cited by students as reasons for changing career goals align with their outcomes expectations about attaining a career as a PI. Several studies designed to examine career interest formation through the lens of SCCT have also shown that social identity influences career interests of biomedical scientists, 15,16,28,33,34 though we did not attempt to analyze the role of social identity in our population, as it is beyond the scope of this study.…”
Section: Changing Career Goalsmentioning
confidence: 99%
“…In addition, individuals with high self-efficacy tend to take responsibility, act innovatively, and understand themselves so that they will choose career aspirations according to their abilities (Pinquart et al, 2004). Career orientation was also found to be associated with career aspirations and to be a reinforcement of one's self-efficacy (Fukada et al, 2019;Argyropoulou et al, 2021;Pshembayeva, 2022;Chatterjee et al, 2023).…”
Section: Discussionmentioning
confidence: 99%